A case study of actual versus desired inclusion of community-derived core concepts into neuroscience courses in different disciplines at a large university - Maita, Isabella; Owens, Melinda T.; Juavinett, Ashley L. (Frontiers in Education, 2024)
Neuroscience is an inherently interdisciplinary and rapidly evolving field. While many universities have neuroscience or related majors, they are highly heterogeneous, and it is unclear how their content aligns with a recent proposal of what ideas make up the field of neuroscience. It is therefore important to document and assess the alignment of neuroscience curricula with core concepts in the field. Recently, a large effort by some members of the neuroscience education community described eight core concepts for undergraduate neuroscience curricula. In this paper, we focus primarily on courses in biology, cognitive science, and psychology at a large university, surveying the recent and current course instructors of these courses to ask them 1) to what extent these community-derived core concepts are incorporated into their classes and 2) to what extent these concepts should be incorporated into their classes. In addition, we map core concepts onto course syllabi. We identify core concepts that are not addressed in these courses and consider barriers to instructors' ability to align course content with core concepts, both within and across disciplines. In this effort, we provide an example for how departments can evaluate their alignment of major requirements with the neuroscience core concepts.